ANALISIS PROSPEK USAHATANI MENTIMUN DI DESA BENTEK LOMBOK UTARA - YUDI HERMAWAN (GANEC SWARA, 2023)
This study aims to determine the income of cucumber farmers in Bentek Village, to determine the efficiency in running cucumber farming in Bentek Village, and to find out the obstacles or obstacles faced by farmers in cucumber farming in Bentek Village. The research was conducted in Bentek Village, Gangga District, North Lombok Regency. Determination of the research area is done by purposive sampling. A total of 30 cucumber farmers in Bentek Village were used as samples in this study by means of a census. The variables measured in this study were the total income of farmers, efficiency in cucumber farming and the obstacles faced by farmers in cucumber farming. In accordance with the first objective, namely knowing the income of farmers in cucumber farming, an analysis of costs and income was carried out. Then to find out the problems faced by farmers, in taking an inventory of existing problems and obstacles, a descriptive analysis was carried out. The results showed: First, the total income of farmers in cucumber farming in Bentek Village, Gangga District, North Lombok Regency is Rp. 43,202,902 /Ha or Rp. 7,099,677 /LGG. Second, the efficiency of cucumber farming in Bentek Village, Gangga District, North Lombok Regency is 1.75, meaning that every one rupiah allocated to this cucumber farming will bring a profit of 75 rupiah. Third, the constraints faced by farmers are pest and disease attack as much as 86.67%, purity standard 96.67%, and erratic weather 73.33%.